Low energy availability and relative energy deficiency in sport: What coaches should know - Charlton, B. T.; Forsyth, S.; Clarke, D. C. (International Journal of Sports Science & Coaching, 2022)
The Female Athlete Triad (Triad) and the more encompassing Relative Energy Deficiency in Sport (RED-S) are disorders caused by low energy availability (LEA). LEA is a state of insufficient energy intake by an athlete relative to their energy expenditure. Persistent LEA results in the deleterious consequences to health and performance that comprise RED-S. With respect to both the Triad and RED-S, researchers have called for more education of those involved with sport, particularly coaches, to help reduce the incidence of these disorders. Recent studies have shown that as few as 15% of coaches are aware of the Triad, with up to 89% unable to identify even one of its symptoms. RED-S is a more recently established concept such that coach knowledge regarding it has only begun to be assessed, but the results of these initial studies indicate similar trends as for the Triad. In this review, we synthesize research findings from 1986 to 2021 that pertains to LEA and RED-S, which coaches should know so they can better guide their athletes.